Improving Access to Family Planning Services in Rorya District, Tanzania: Qualitative Findings from A Pilot Study (Tanzania Medical Journal, 2021)
BackgroundAccess to modern family planning methods is essential for African women to avoid repeated pregnancies, and the subsequent risk of maternal mortality, particularly in rural contexts. This study addressed the gap in access to family planning services for women living in a rural district of northern Tanzania.ObjectivesIn this pilot study, we trained community health workers to educate couples, distribute condoms and oral contraceptives, and refer women and men for more advanced methods of family planning. The purpose of this study was to explore the views of community members, nurses, and policymakers to this project to improve access to modern family planning methods, to understand the barriers and solutions for accessing family planning services in this rural context.MethodsTwenty focus group discussions were held separately with women, men, community health workers, nurses and policymakers (total 173 participants) from across the district. The focus group transcripts were subjected to a thematic analysis by the first author through repeated readings focusing on the barriers and solutions to accessing family planning services in Rorya District. ResultsThe barriers to family planning access were most commonly negative male attitudes towards women using family planning methods. The community held myths regarding methods, institutional barriers impeding access and specific family planning method challenges were also problematic. Solutions focused on community health education, provider training, reliable supply of family planning methods in the community, and free access to these methods.ConclusionThe community members, nurses and policymakers interviewed about this project agree that community health workers can successfully provide family planning education and basic methods to community members, and refer couples for more advanced methods. Challenges remain to ensure the supply of contraceptive methods is sustainable, and that male partners are engaged and supportive. The four pillars of a successful program in family planning are community-based health education, training of nurses in advanced methods, consistent supply of family planning methods and provision of free supplies to the population.